Polyimide composite film containing adhesive layer and preparation method thereof
By applying and pre-applying an adhesive layer onto the polyimide (PI) film to form a polyimide composite film, the cost and performance problems of PI film in the automotive and photovoltaic fields are solved, and a more efficient and durable composite film is achieved.
Patent Information
- Application Number
- CN202411840776.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The application of existing polyimide (PI) films in the automotive industry and photovoltaic fields is limited by their high cost, brittleness, water vapor transmittance and water absorption, and their inability to resist high temperature and high humidity aging.
The thermoset or semi-cured adhesive is applied to the PI film or other polymer film by the coating process, and pre-sticked by the hot roll pasting process to form a polyimide composite film containing the adhesive layer.
This method simplifies the process, realizes continuous production, reduces costs, and improves the tear strength, elongation, water resistance and aging resistance of the composite film.
Smart Images

Figure BDA0005187920530000091 
Figure HDA0005187920560000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyimide composite films, and in particular to a polyimide composite film containing an adhesive layer and a preparation method thereof. Background Art
[0002] Polyimide (PI) film has the best thermal stability, chemical corrosion resistance, mechanical properties and electrical insulation properties among polymer films. It is often used in the electronics industry, aerospace, automotive parts and other fields, such as motor slot insulation, cable wrapping materials, printed circuit boards, etc.
[0003] However, the price of PI film is relatively high, which limits its wide application in the automotive industry and photovoltaic field. In addition, although PI film has high strength, it has certain brittleness, showing low elongation and tear strength, which is limited in the bending process or special-shaped parts processing. Moreover, PI film has high water vapor permeability and water absorption and is not resistant to high temperature and high humidity aging, which further limits its application in automobiles, especially in the new energy automobile industry.
[0004] Products composited with polyimide (PI) films and other polymer films have been used in many fields. Patent CN112996664B uses a polyamic acid solution co-extrusion process to prepare a PI multilayer composite film of fluorine-containing resin, which greatly reduces the dielectric constant and water absorption of the PI film. In addition, there is also a process method of coating the base film with PI slurry. The existing methods for preparing PI composite films all have the problems of complex processes and high costs. Therefore, it is of great significance to develop a method for preparing a PI composite film with simple process, continuous production and high production efficiency. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a polyimide composite film containing an adhesive layer and a preparation method thereof. A thermosetting or semi-curing adhesive is coated on a polyimide (PI) film or other polymer films through a coating process, and then pre-laminated by a hot roller lamination process to composite the PI film with other polymer films. The process is simple, continuous production is possible, and production efficiency is high.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0007] S1. providing a polyimide film and a polymer film to be composited;
[0008] S2. When the thickness of the polyimide film is greater than or equal to the thickness of the polymer film, a layer of adhesive is coated on the polyimide film, and after drying, the adhesive layer is pre-laminated onto the polymer film by hot roller lamination;
[0009] When the thickness of the polyimide film is less than the thickness of the polymer film, a layer of adhesive is coated on the polymer film, and after drying, the adhesive layer is pre-laminated on the polyimide film by hot roller lamination;
[0010] Wherein, the raw material components of the adhesive layer include, by weight: 30-80 parts of polyester resin, 10-50 parts of epoxy resin, 5-50 parts of filler, and 3-10 parts of curing agent;
[0011] S3. After aging treatment, a polyimide composite film containing an adhesive layer is obtained.
[0012] The present invention coats a thermosetting or semi-curing adhesive on a polyimide (PI) film or other polymer film through a coating process, and then pre-laminates the PI film with other polymer films through a hot roller lamination process. The process is simple, continuous production is possible, and production efficiency is high. The composite film prepared by the method of the present invention has a greater cost advantage than a PI film of the same thickness, while enhancing the tear strength and elongation, and reducing the water vapor permeability and water absorption rate; the composite film can also have the mechanical properties, chemical corrosion resistance and insulation properties of the PI film itself; the composite film also has excellent interlayer bonding and aging resistance, and can adapt to applications in different working conditions.
[0013] Furthermore, the polyester resin has a glass transition temperature of -20°C to 50°C, a number average molecular weight of 5000 to 50000, and a solid acid value of less than 5 mgKOH / g.
[0014] Furthermore, the drying process is carried out at a temperature of 60-150°C and a time of 2-5 minutes;
[0015] And / or, the aging treatment is performed at a temperature of 20-80°C and for a time of 6-120 hours;
[0016] And / or, the pressure of the hot roller lamination is 0.1-0.5 MPa and the temperature is 20-120°C.
[0017] Furthermore, the polyimide film or the polymer film is subjected to corona or plasma treatment before coating to improve bonding performance.
[0018] Furthermore, the polyimide film has a thickness of 5-125 μm;
[0019] And or, the polymer film has a thickness of 5-400 μm;
[0020] And or, the thickness of the adhesive layer is 5-40 μm.
[0021] Further, the curing agent is one or more of toluene diisocyanate (TDI) and its dimer and trimer, diphenylmethane diisocyanate (MDI) and its dimer and trimer, hexamethylene diisocyanate (HDI) and its dimer and trimer, isophorone diisocyanate (IPDI) and its dimer and trimer;
[0022] And / or, the mass ratio of the curing agent to the polyester resin is 1:(7-30). When the curing agent content is too high, the adhesive reacts too quickly, the composite film preparation process window is shortened, and excessive curing agent will greatly reduce the ability to resist high temperature and high humidity; when the curing agent content is too low, the degree of cross-linking of the adhesive is too low, and the interlayer bonding force of the composite film is low.
[0023] Furthermore, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, bisphenol A novolac epoxy resin, and phenol biphenyl epoxy resin.
[0024] Furthermore, the average particle size of the filler is 0.5-10 μm, and the filler is one or more of silicon dioxide, metal oxides, and phosphorus flame retardants;
[0025] The silicon dioxide is one or more of white carbon black, wollastonite, mica and kaolin;
[0026] The metal oxides are aluminum hydroxide and / or magnesium hydroxide;
[0027] The phosphorus-based flame retardants include one or more of diethyl aluminum hypophosphite, ammonium polyphosphate, and aluminum hypophosphite.
[0028] Furthermore, the polymer film is a polyethylene terephthalate (PET) film, a polybutylene terephthalate (PBT) film, a polyethylene naphthalate (PEN) film, a polyphenylene sulfide (PPS) film, a polycarbonate (PC) film, a polyetherimide (PEI) film, a polyphenylene oxide (PPO) film, a polyamide (PA) film or a polymethyl methacrylate (PMMA) film.
[0029] The second aspect of the present invention provides a polyimide composite film containing an adhesive layer prepared by the preparation method described in the first aspect.
[0030] Beneficial effects of the present invention:
[0031] The present invention coats a thermosetting or semi-curing adhesive on a polyimide (PI) film or other polymer films through a coating process, and then pre-laminates the film through a hot roller lamination process to composite the PI film with other polymer films. The process is simple, continuous production is possible, and production efficiency is high.
[0032] The composite film prepared by the method of the present invention has a greater cost advantage than a PI film of the same thickness, while enhancing the tear strength and elongation and reducing the water vapor permeability and water absorption.
[0033] The composite film of the invention has the mechanical properties, chemical corrosion resistance and insulation properties of a PI film of the same thickness.
[0034] The composite film of the present invention also has excellent interlayer bonding strength and aging resistance, and can be applied in different working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is a schematic structural diagram of a polyimide composite film containing an adhesive layer of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment relates to a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0040] Dissolve 80 parts of polyester resin and 20 parts of bisphenol A epoxy resin in butanone solvent, then add 40 parts of filler diethyl aluminum hypophosphite to the solution, stir at high speed to evenly blend the filler and resin, then add 5 parts of curing agent HDI trimer, stir evenly and apply on the line. Evenly apply a 20um thick adhesive layer of dry glue on a 188μm thick PET film, dry at 120℃ for 4min, then apply a 75μm thick PI film to the adhesive surface with a hot roller at 100℃ and 0.4MPa, and then roll it up. After rolling up, mature at 60℃ for 48h to obtain a composite film of polyimide film / adhesive layer / polymer film, such as Figure 1 The polyester has a glass transition temperature (Tg) of 10°C to 20°C, a number average molecular weight (Mn) of 20,000 to 30,000, and a solid acid value of less than 2 mgKOH / g.
[0041] Example 2
[0042] This embodiment relates to a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0043] Dissolve 80 parts of polyester resin and 20 parts of bisphenol A epoxy resin in butanone solvent, then add 40 parts of filler diethyl aluminum hypophosphite to the solution, stir at high speed to make the filler and resin blend evenly, then add 5 parts of curing agent HDI trimer, stir evenly and apply on the line. Evenly apply a 20um thick adhesive layer of dry glue on a 100μm thick PI film, dry it at 120℃ for 4min, then apply a 50μm thick PET film hot roller to the adhesive surface at 100℃ and 0.4MPa, and then roll it up. After rolling, mature at 60℃ for 48h. Among them, the glass transition temperature (Tg) of the polyester value is 10℃~20℃, the number average molecular weight (Mn) is 20000~30000, and the solid acid value is less than 2mgKOH / g.
[0044] Example 3
[0045] This embodiment relates to a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0046] Dissolve 80 parts of polyester resin and 20 parts of bisphenol A epoxy resin in butanone solvent, then add 30 parts of filler diethyl aluminum hypophosphite to the solution, stir at high speed to make the filler and resin blend evenly, then add 4 parts of curing agent HDI trimer and 3 parts of HDI dimer, stir evenly and apply on the line. Evenly apply a 20um thick adhesive layer of dry glue on a 350μm thick PET film, dry it at 120℃ for 4min, then apply a 100μm thick PI film hot roller to the adhesive surface at 100℃ and 0.4MPa, and then roll it up. After rolling, mature at 60℃ for 48h. Among them, the glass transition temperature (Tg) of the polyester value is 10℃~20℃, the number average molecular weight (Mn) is 20000~30000, and the solid acid value is less than 2mgKOH / g.
[0047] Example 4
[0048] This embodiment relates to a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0049] Dissolve 80 parts of polyester resin and 20 parts of bisphenol A epoxy resin in butanone solvent, then add 40 parts of filler diethyl aluminum hypophosphite to the solution, stir at high speed to make the filler and resin blend evenly, then add 8 parts of curing agent HDI dimer, stir evenly and apply on the line. Evenly apply a 20um thick adhesive layer of dry glue on a 250μm thick PET film, dry it at 120℃ for 4min, then apply a 75μm thick PI film hot roller to the adhesive surface at 100℃ and 0.4MPa, and then roll it up. After rolling, mature it at 60℃ for 48h. Among them, the glass transition temperature (Tg) of the polyester value is 10℃~20℃, the number average molecular weight (Mn) is 20000~30000, and the solid acid value is less than 2mgKOH / g.
[0050] Example 5
[0051] This embodiment relates to a method for preparing a polyimide composite film containing an adhesive layer, comprising the following steps:
[0052] Dissolve 70 parts of polyester resin and 30 parts of bisphenol A epoxy resin in butanone solvent, then add 30 parts of filler diethyl aluminum hypophosphite to the solution, stir at high speed to make the filler and resin blend evenly, then add 4 parts of curing agent HDI trimer, stir evenly and apply on the line. Evenly apply a 20um thick adhesive layer of dry glue on a 50μm thick PI film, dry it at 120℃ for 4min, then apply a 50μm thick PET film to the adhesive surface with a hot roller at 100℃ and 0.4MPa, and then roll it up. After rolling, mature it at 60℃ for 48h. Among them, the glass transition temperature (Tg) of the polyester value is 10℃~20℃, the number average molecular weight (Mn) is 20000~30000, and the solid acid value is less than 2mgKOH / g.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that the amount of curing agent added is 20 parts, and the other steps and parameters remain unchanged.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 2 is that: 95 parts of polyester resin and 5 parts of bisphenol A epoxy resin are used, and other steps and parameters remain unchanged.
[0057] Comparative Example 3
[0058] The difference between this comparative example and Example 3 is that no filler is added, the curing agent is 8 parts of HDI dimer, and other steps and parameters remain unchanged.
[0059] Comparative Example 4
[0060] This comparative example is a PI film with a thickness of 100 μm.
[0061] The performance of the films obtained in the examples and comparative examples was tested, and the results are shown in Table 1. The specific test method is:
[0062] Shear strength: Cut the sample into 25*12.5mm specimens, then take two 25mm wide aluminum plates, evenly apply structural adhesive, and overlap the coated parts at the center of the sample. Let the fixed sample stand at room temperature for 24 hours, then bake at 80℃ for 12 hours to mature. After the sample is matured, take it out and let it cool at room temperature for 12 hours. Use the tensile machine fixture to clamp the sample, stretch it at a speed of 5mm / min, test the maximum force, and calculate the shear strength based on the actual overlap area.
[0063] Touch adhesion: Cut the sample into 25*12.5mm specimens, then take two T-shaped aluminum blocks, evenly apply structural glue, and overlap the glued parts at the center of the specimen. Let the fixed sample stand at room temperature for 24 hours, then bake at 80℃ for 12 hours to mature. After the sample is matured, take it out and let it cool at room temperature for 12 hours. Use the tensile machine fixture to clamp the sample, stretch it at a speed of 5mm / min, test the maximum force, and calculate the pull-out strength based on the actual overlap area.
[0064] Water absorption rate: Bake the sample at 100℃ for 1h, weigh the mass W1, then soak it in water for 24h, wipe off the surface moisture and weigh its mass W2, calculate the water absorption rate = (W2-W1) / W1.
[0065] High-pressure cooking test: The sample is placed in a high-pressure cooking aging box, and the aging test conditions are: 121°C, 2 atmospheres, and 100% RH.
[0066] High temperature and high humidity aging test: Place the sample in a high temperature and high humidity aging box. The aging test conditions are: 85°C, 85% RH, 1000h.
[0067] Thermal shock aging test: Place the sample in a thermal shock aging box. The aging test conditions are: -40℃~105℃ alternating temperature, 2h per cycle, 500 cycles, a total of 1000h.
[0068] Neutral salt spray aging test: Place the sample in a neutral salt spray aging chamber. The aging test conditions are: temperature 35°C, humidity 85% RH, 5% NaCl solution, and continuous spraying for 72 hours.
[0069] Table 1
[0070]
[0071] It can be seen from Table 1 that the polyimide composite films provided in Examples 1-5 have excellent shear strength and tensile strength, among which the composite film of Example 3 has a shear strength of up to 13 MPa, a tensile strength of up to 13 MPa, a water absorption rate of only 1.2%, and qualified high temperature and humidity, hot and cold shock and neutral salt spray resistance performance, with excellent comprehensive performance.
[0072] Compared with Example 1, in Comparative Example 1, the amount of curing agent added is too much, the adhesive reacts too quickly, and the composite film preparation process window is shortened, resulting in the polyimide composite film having unqualified high pressure cooking resistance and high temperature and high humidity performance.
[0073] Compared with Example 2, in Comparative Example 2, the amount of polyester resin added is too much and the amount of epoxy resin added is too little, resulting in insufficient crosslinking of the adhesive layer. The shear strength and tensile strength of the prepared polyimide composite film are low, and the high pressure cooking resistance test is unqualified.
[0074] Compared with Example 3, in Comparative Example 3, no filler was added, resulting in lower shear strength and tensile strength of the prepared polyimide composite film.
[0075] Compared with the 50μmPI film composited with the 50μmPET film in Example 5, the comparative example 4 was tested with a 100μmPI film, and its high pressure cooking and high temperature and high humidity aging tests failed. However, the composite film was supported by the PET film and showed good hydrolysis resistance.
[0076] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a polyimide composite film containing an adhesive layer, characterized in that: The steps include: S1. providing a polyimide film and a polymer film to be composited; S2. When the thickness of the polyimide film is greater than or equal to the thickness of the polymer film, a layer of adhesive is coated on the polyimide film, and after drying, the adhesive layer is pre-laminated onto the polymer film by hot roller lamination; When the thickness of the polyimide film is less than the thickness of the polymer film, a layer of adhesive is coated on the polymer film, and after drying, the adhesive layer is pre-laminated on the polyimide film by hot roller lamination; Wherein, the raw material components of the adhesive layer include, by weight: 30-80 parts of polyester resin, 10-50 parts of epoxy resin, 5-50 parts of filler, and 3-10 parts of curing agent; S3. After aging treatment, a polyimide composite film containing an adhesive layer is obtained.
2. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The polyester resin has a glass transition temperature of -20°C to 50°C, a number average molecular weight of 5000 to 50000, and a solid acid value of less than 5 mgKOH / g.
3. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The drying process is carried out at a temperature of 60-150°C and a time of 2-5 minutes; And / or, the aging treatment is performed at a temperature of 20-80°C and for a time of 6-120 hours; And / or, the pressure of the hot roller lamination is 0.1-0.5 MPa and the temperature is 20-120°C.
4. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, wherein: The polyimide film or the polymer film is subjected to corona or plasma treatment before coating.
5. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The thickness of the polyimide film is 5-125 μm; And or, the polymer film has a thickness of 5-400 μm; And or, the thickness of the adhesive layer is 5-40 μm.
6. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The curing agent is one or more of toluene diisocyanate and its dimer and trimer, diphenylmethane diisocyanate and its dimer and trimer, hexamethylene diisocyanate and its dimer and trimer, isophorone diisocyanate and its dimer and trimer; And / or, the mass ratio of the curing agent to the polyester resin is 1:(7-30).
7. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, bisphenol A novolac epoxy resin, and phenol biphenyl epoxy resin.
8. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The average particle size of the filler is 0.5-10 μm, and the filler is one or more of silicon dioxide, metal oxides, and phosphorus flame retardants; The silicon dioxide is one or more of white carbon black, wollastonite, mica and kaolin; The metal oxides are aluminum hydroxide and / or magnesium hydroxide; The phosphorus-based flame retardants include one or more of diethyl aluminum hypophosphite, ammonium polyphosphate, and aluminum hypophosphite.
9. The method for preparing a polyimide composite film containing an adhesive layer according to claim 1, characterized in that: The polymer film is a polyethylene terephthalate film, a polybutylene terephthalate film, a polyethylene naphthalate film, a polyphenylene sulfide film, a polycarbonate film, a polyetherimide film, a polyphenylene ether film, a polyamide film or a polymethyl methacrylate film.
10. A polyimide composite film containing an adhesive layer obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polyimide composite films with excellent dielectric properties and their preparation methods
CN112996664B
Adhesive and adhesive film using same
CN117126635A
Substrate-free thermosetting flame-retardant adhesive film as well as preparation method and application thereof
CN117903736A
Heat resistant polyester hybrid film, and method forpreparing them
KR1020010003919A
Poly imide / poly ethylene terephthalate hybrid films with good ahdesion, and method for preparing them
KR1020020065777A